Effect of neonatal seizure burden and etiology on the long‐term outcome: data from a randomized, controlled trial - Sara K. Trowbridge; Lois O. Condie; Jessica R. Landers; Ann M. Bergin; Patricia E. Grant; Kalpathy Krishnamoorthy; Valerie Rofeberg; David Wypij; Kevin J. Staley; Janet S. Soul; for the Boston Bumetanide Trial Group (Wiley, 2023)
Abstract Background Neonatal seizures are common, but the impact of neonatal seizures on long‐term neurologic outcomes remains unclear. We addressed this question by analyzing data from an early‐phase controlled trial of bumetanide to treat neonatal seizures. Methods Neonatal seizure burden was calculated from continuous video‐electroencephalogram data. Neurologic outcome was determined by standardized developmental tests and postneonatal seizure recurrence. Results Of 111 enrolled neonates, 43 were randomized to treatment or control groups. There were no differences in neurologic outcomes between treatment and control groups. A subgroup analysis was performed for 84 neonates with acute perinatal brain injury (57 hypoxic-ischemic encephalopathy [HIE], 18 stroke, 9 intracranial hemorrhage [ICH]), most of whom (70%) had neonatal seizures. There was a significant negative correlation between seizure burden and developmental scores (p < 0.01). Associations between seizure burden and developmental scores were stronger in HIE and stroke groups compared with ICH (p < 0.05). Conclusion Bumetanide showed no long‐term beneficial or adverse effects, as expected based on treatment duration versus duration of neonatal seizures. For neonates with perinatal brain injury, higher neonatal seizure burden correlated significantly with the worse developmental outcome, particularly for ischemic versus hemorrhagic brain injury. These data highlight the need for further investigation of the long‐term effects of both neonatal seizure severity and etiology.